Preoperative brain μ-opioid receptor availability predicts weight development following bariatric surgery in women - Karlsson Henry K; Tuominen Lauri; Helin Semi; Salminen Paulina; Nuutila Pirjo; Nummenmaa Lauri (AMER SOC CLINICAL INVESTIGATION INC, 2022)
Bariatric surgery is the most effective method for weight loss in morbid obesity. There is significant individual variability in the weight loss outcomes, yet factors leading to postoperative weight loss or weight regain remain elusive. Alterations in the mu-opioid receptor (MOR) and dopamine D2 receptor (D2R) systems are associated with obesity and appetite control, and the magnitude of initial brain receptor system perturbation may predict long-term surgical weight loss outcomes. We tested this hypothesis by studying 19 morbidly obese women (mean BMI 40) scheduled to undergo bariatric surgery. We measured their preoperative MOR and D2R availabilities using positron emission tomography with [11C]carfentanil and [11C]raclopride, respectively, and then assessed their weight development association with regional MOR and D2R availabilities at 24-month follow-up. MOR availability in the amygdala consistently predicted weight development throughout the follow-up period, but no associations were found for D2R. This is the first study to our knowledge to demonstrate that neuroreceptor markers prior to bariatric surgery are associated with postoperative weight development. Postoperative weight regain may derive from dysfunction in the opioid system, and weight loss outcomes after bariatric surgery may be partially predicted based on preoperative brain receptor availability, opening up new potential for treatment possibilities.